KIC 10855535: An Elegant δ Scuti Pulsator with Amplitude and Phase Modulation - Li-xian Shen; Ali Esamdin; Cheng-long Lv; Hao-zhi Wang; Tao-zhi Yang; Rivkat Karimov; Shuhrat A. Ehgamberdiev; Hu-biao Niu; Jin-zhong Liu (The Astrophysical Journal)
We investigated the pulsating behavior of KIC 10855535 using Kepler 4 yr long-cadence data. Two independent frequencies were detected: a pulsation frequency F0 = 17.733260(5) day ^−1 and a low frequency f _8 = 0.412643(8) day ^−1 . We identify F0 as the fundamental frequency, at which an equidistant quintuplet is centered, suggesting that the star orbits in a binary system. The fitted orbital parameters align well with those reported in previous literature. Long-term phase modulation caused by binarity has been confirmed by considering the light curve from the Transiting Exoplanet Survey Satellite. By removing the light-time effect, we measured a linear change in period of order $\dot{P}/P\simeq 1.44× {10}^{-7}\,{yr}^{-1}$ , a value that could be indicative of stellar evolution. The star also exhibits a gradual and stable amplitude growth, thereby raising the possibility of structural changes during its evolution. We attributed f _8 and its two harmonics to rotation and surface spots, with further analysis suggesting characteristics evolving over time. Based on this hypothesis, KIC 10855535 may rotate slowly for its type, with a speed of 37(2) km s ^−1 . Overall, KIC 10855535 presents an exceptionally clean spectrum and a relatively slow rotation as a δ Sct pulsator, exhibiting a single pulsation mode that undergoes both amplitude and phase modulation.